Ludzkie cierpienie w świetle wypowiedzi starotestamentalnych hagiografów - Szwarc, Urszula (The Biblical Annals, 2017)
In the introduction the author states that man’s suffering began when be was first disobedient to God. In the first part she speaks about man’s physical and spiritual suffering, about sufferings connected with natural calamities, wars, and other misfortunes. In part two she draws the reader’s attention to the problem of undeserved suffering, to its source (God’s mysterious will) and sense (a puryfying and rewarding character of it). In the third part she deals with man’s attitude towards suffering (trust in God, peace, patience, charity towards other people).